Relationship between vocal intensity, pitch and nasality in cleft palate speakers - Asthana, Pamela (Journal of All India Institute of Speech and Hearing)
This study was conducted to find out the effect of pitch variaton and the effect of intensity variation on the degree of nasality perceived by the listeners. The different pitch levels taken into consideration were habitual pitch, 100 Hz above habitual pitch and 30 Hz below’ habitual pitch. The different intensity levels were 65 dB, 70 dB and 80 dB SPL. Vowels [a, i, u, e, o] and [ae] were Chosen for phonation to represent the high, intermediate and low positions of the front and back vowels.